Seismic Behavior of Lisbon Mixed Masonry-RC Buildings With Historical Value: A Contribution for the Practical Assessment - Milosevic, Jelena; Bento, Rita; Cattari, Serena (Frontiers in Built Environment, 2018)
The fact that linear analysis is still the most used procedure in the design engineering offices, studies which addresses issues associated to the estimation of the structural behavior factor values are relevant. In this study, the behavior factor of a particular type of mixed masonry-reinforced concrete buildings in Lisbon is estimated. The typology chosen in this study represents 30% of building stock in Lisbon; these buildings were built between 1930-60 and thus were designed without considering the seismic-design requirements proposed in current codes. The evaluation of the behavior factors was based on the use of nonlinear static analyses, performed in the form of the sensitivity analysis and following the criteria proposed in the current seismic codes and literature. In the scope of the sensitivity analysis, aleatory and epistemic uncertainties have been considered in terms of the mechanical parameters and structural details, respectively with the aim to take into account different characteristics of the structures. In order to derive the most reliable values of the behavior factor for this typology, extensive research in terms of the historical information, structural characterization and definition of the mechanical parameters has been performed. The study indicates that the final values of behavior factor are low and depend most on the type of connections between structural walls. Although the obtained values of the behavior factor for this typology match well with the ones proposed in most recent seismic codes, it is recommended that the assessment of such factor of a specific class for a particular structural type building should always be careful evaluated.